Socioeconomic factors and its role in emotion regulation in children from a socio-ecological perspective: a systematic literature review - Mohamad Omar Ihsan Razman,; Suzana Mohd Hoesni, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Socioeconomic status (SES) has been shown to affect children in their ability to regulate emotions. Factors related to SES such as parenting behavior and chaotic living environment is linked to decreased emotion regulation (ER) in children. This review explores the role of SES in the development of ER in children. Two online databases were searched and returned 261 articles. After the process of screening and eligibility according to PRISMA guidelines, 10 articles were included in this review. Results from this systematic review suggest that there is a significant relationship between SES and ER and a correlational, predictive and longitudinal relationship between SES and ER in children was found. Three main themes were found associated with SES and ER in children which were family income, parental and environmental factor. SES is an essential factor associated with the development of ER in children. Findings from the study supports the importance of targeted social-emotional intervention for lower SES children.